Deus deu o golpe? uma análise do discurso religioso neopentecostal no cenário político brasileiro do impeachment de Dilma Rousseff - Gerhardt, Edigar Barraqui (2020)
The study of religious discourse and its mechanisms for producing meaning has proved to be of great relevance, especially with regard to the Brazilian political scene, where this type of discourse (particularly that of the neo-Pentecostal aspect), markedly theocentric and, at times, , a moralist, finds himself increasingly rooted and with great representativeness, mainly in the decision-making spheres of politics (despite the premise of the secularity of the State), acting as a shaper of public opinion and self justifying himself based on ultraconservative ideals. In 2016, the context of the process that led to the impeachment of President Dilma Rousseff was also marked by religious based speeches. Thus, the objective of this research is to verify to what extent the neo Pentecostal religious discourse contributed to legitimize and influence political positions in the process that culminated in the impeachment of Dilma Rousseff, describing the strategies for the formation of this type of discourse and identifying its interdiscursive crossings, considering it as an intricate discursive formation in a conservative ideological formation. The theoretical perspective used in this study is the French Discourse Analysis, mainly from the works of Michel Pechêux and Dominique Maingueneau, and from the categories: Production Conditions, Discursive Formation, Ethos, Scenography, Constituent Discourses and Semantic Coercion Systems. The methodological path adopted was the organization and analysis of an archive, composed of speeches by political-religious leaders, aligned with the neo-Pentecostal discourse, which played a strategic role in mobilizing and convincing pro impeachment. As a result, it is possible to verify that the analyzed speeches seem to conform to the neo-Pentecostal religious discourse insofar as they present ideological inscriptions of that discourse, acting in order to sacralize and validate all the action of the process that led to the withdrawal of President Dilma Rousseff from the government, making it divine and unquestionable to the senses of a large mass of evangelicals in the country.